Doktrin Putusan Bisnis Dalam Kasus Hak Partisipasi (Participating Interest) Pada Anak Perusahaan PT. Pertamina (Persero) - Fadjriaty, Dessy (Fakultas Hukum Universitas Trisakti, 2022)
The Business Judgement Rule is one of the doctrines in the limited company that protects directors from personal liability, when they have acted in good faith, have acquired sufficient information, and can be trusted that the action taken is the best in the interests of the company, as stipulated in Article 97, paragraph 5, of the 2007 Act No. 40 on the Limited Company. What is the responsibility of the First PT Directorate (Persero) in the case of the acquisition of participating interests carried out by the PT. First Hulu Energy as a subsidiary of his company. As for research methods performed normatively using secondary legal material, then the data processing is performed qualitatively, with the conclusion being drawn with deductive logic. Based on the analysis it is known that the management of PT Pertamina is not responsible for what is done by the subsidiary as a business decision in accordance with the doctrine of business judgement rule in the case. The Business Judgement Rule doctrine is vulnerable to its application in corporate law that is sometimes not well understood.